2015
DOI: 10.1177/0272989x15597224
|View full text |Cite
|
Sign up to set email alerts
|

Is the “Heart Age” Concept Helpful or Harmful Compared to Absolute Cardiovascular Disease Risk? An Experimental Study

Abstract: Background: Cardiovascular disease (CVD) prevention guidelines are generally based on the absolute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 37 publications
3
45
0
2
Order By: Relevance
“…They are also consistent to a large extent with a previous qualitative study that found that heart age can motivate lifestyle change [27]. We did not find decreased perceived credibility to this format of presentation of risk scores reported by that and other study [26], although if much higher than the actual age, ‘heart age’, like the genetic risk scores, can lead to some fatalistic views about CVD risk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They are also consistent to a large extent with a previous qualitative study that found that heart age can motivate lifestyle change [27]. We did not find decreased perceived credibility to this format of presentation of risk scores reported by that and other study [26], although if much higher than the actual age, ‘heart age’, like the genetic risk scores, can lead to some fatalistic views about CVD risk.…”
Section: Discussionsupporting
confidence: 92%
“…One recent randomised controlled trial found ‘heart age’ to be more effective than other types of individual’s modelled CVD risk in reducing risk scores [24]. Two studies, one experimental [26] and one qualitative [27] have found decreased perceived credibility for risk scores presented in this way, although the latter found it could still motivate lifestyle change. With increasingly available genetic data it has also been suggested that CVD risk information might be more effective when based on genetic information [2830].…”
Section: Introductionmentioning
confidence: 99%
“…Four RCTs looked at the effect of heart age/cardiovascular age on patient behaviour. Bonner et al 16 showed that at 2 weeks after intervention, there was a positive change in lifestyle. The control group, who were told absolute cardiovascular risk, had a 15% smoking cessation rate.…”
Section: Resultsmentioning
confidence: 99%
“…This was mostly due to the heterogeneity of the recruitment, measurements of patient behaviour and the use of different age calculators. Recruitment included GP practices,15 18 20 Foulds 2015 19 college campuses (Lipkus 2007), online access research panels (Souretti 2010, Dammon OC 2018), market research company recruitment,16 smoking cessation clinics,21 25 hospital records (Drummond 2014,22) employee from recycling company,26 telephone directory24 and Spanish public health workers 17. Therefore, a meta-analysis could not be performed on the data.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are compatible with previous research on the meaning of risk in CVD and other health areas. In CVD, previous studies have found more engagement and emotional reactions to salient risk formats such as heart age [28,29], but this may be counteracted by questioning risk results that don't match expectations [11,30]. Subjective perceptions of the need for medication may be focused on treating individual risk factors [31] and do not necessarily match actual estimates of CVD event reduction.…”
Section: Discussionmentioning
confidence: 96%